The resources of hilsa shad, Hilsa ilisha (Hamilton), along the northeast coast of India - Reuben, S; Dan, S S; Somaraju, M V; Philipose, V; Sathianandan, T V (Indian Journal of Fisheries, 2011)
The results of .. study on the fishery, biology, exploitation and mortaIity of hils a shad (Hilsa ili.Yha) arepresented. The average annual landing of Hilsa ilisha for 1979 - 88 was 5 710 tonnes fonning 0.4% of the totallandings. The major craft and gears and the contributions of different states are presented. Age at first maturitywas estimated as 1.98 years. The details of spawning migrations, maturity stages and fecundity are discussed.The total mortality, natural mortality and fishing mortality coefficients were ob.tained as 1.71. 0.704 and 0.9444respectively. The present yield of 4168 tonnes was the same as tbeestimated MSY indicating the optimum levelof exploitation